Competing policy imperatives in Post-Apartheid South Africa: An analysis of the effects and larger significance of ESKOM restructuring on the South African automotive industry, 2005-2014 - Sibuyi, Lucas Nkosana (Rhodes University, Faculty of Humanities, Department of Sociology)
The state has played an indispensable, major role in the industrialisation of South Africa, and its transformation from an economy of agriculture and mining to one based on manufacturing and services by the 1970s. Large state-owned corporations in communications and transportation, finance, industry and power have been key to this process, which also involved an extensive (and racist form of) import substitution industrialisation (ISI) from the 1920s. The 1970s saw a shift towards neoliberal policies, first under the National-Party-led apartheid government and then under the African-National-Congress-led democratic government formed in 1994. Since the 1980s, this restructuring has profoundly affected state-owned enterprises (SOEs), including the monopoly electricity utility ESKOM, and manufacturing industries, such as the automotive sector. This thesis examines the evolution of and interaction between different areas of neoliberal policy, and their evolution over time through a consideration of the relationship between the restructuring of SOEs and manufacturing, with a focus on ESKOM and autotomotives respectively. Relying on interviews with senior officials, policymakers, union leaders and industrialists, as well as primary documents, the study examines the responses of OEMs in South Africa (BMW, Ford, General Motors, Mercedes Benz/Daimler, Nissan, Toyota and Volkswagen) to ESKOM's actions, and analyses the root of these actions. It argues that while restructuring has been framed by a common framework, policy development and implementation is not coordinated or cohesive. ESKOM, for example, gutted investment in electricity and maintenance generation capacity to become profitable and create space for Independent Power Providers (IPPs) "“ neoliberal measures for which it was rewarded and lauded. This took place at a time when national policy emphasised the need to grow manufacturing and attract direct investment by creating an investor-friendly climate resting on infrastructure. It also took place when the Department of Trade and Industry (DTI) rolled out highly successful plans "“ also praised and rewarded "“ to help adjust automotives to open markets; the sector grew much larger than under ISI, while other sectors like textiles collapsed. ESKOM's measures, however, led to a rapid decline in the capacity and stability of the power system, and directly contradicted the drive to expand and globalise manufacturing, in which automotives was now the leading edge. Corruption in the utility worsened, much of it through subcontracting measures rooted in neoliberal reforms, but this did not cause the basic problems. It is argued that this situation of competing policy imperatives reflects deeper, long-term problems in the South African state, including contradictory policies, uneven capacity and a lack of coordination. For example, there was no coordination between the DTI and stakeholder departments that regulate ESKOM, being the shareholder ministry, the Department of Public Enterprises (DPE) and its policy ministry, and the Department of Mineral Resources and Energy (DMRE). These types of problems did not start postapartheid, and post-1994 reforms have not adequately addressed them. What exists is not a "developmental" state, as policymakers hope, but a fractured state of an intermediate type that combines "developmental" and "predatory" features in a oneparty dominant system in which lines between ruling party and state blur, and state resources are leveraged for elite class formation. Such was the case under apartheid skippered by the NP, with Afrikanerisation, and it continues today post-apartheid under the ANC with BEE. Major reforms are needed, but not just in SOE governance or budgets, as many have suggested. If we are to take the nation forward, the basic design of the state must be reformed. The state needs professionalised, coherent policy-making and implementation, proper coordination of state entities and hard decisions. It should manage high levels of public infrastructure, guarantee political stability and credit ratings, and provide policy certainty and predictability. Without big reforms it will remain a chronic underperformer.
Keywords: Eskom (Firm); South Africa Colonial influence; Electric power Conservation -- South Africa; Electric utilities Government ownership -- South Africa; Electric utilities Privatization -- South Africa; Import substitution -- South Africa; Government business enterprises -- South Africa